A RETROSPECTIVE STUDY ON TREATMENT OF CHRONIC DIABETIC FOOT ULCERS WITH VASCULAR SURGERY, MICROSURGERY, AND SUPRAMICROSURGERY FOR PREVENTION OF AMPUTATION. - Prakash , Kumar; Sanjay, Kumar (Student's Journal of Health Research Africa, 2023)
Introduction: About 2.5% of people with diabetes develop diabetic foot ulcers, which can cause serious infections and necessitate amputation. These ulcers are to blame for extended hospital stays and comorbidities brought on by untreated diabetic foot ulcers. Simple, conservative methods can be used to treat small, superficial ulcers. However, surgery is necessary to treat exposed bones or tendons in order to avoid osteomyelitis. Reconstructive surgery is frequently required, occasionally in conjunction with revascularization of the foot. Methods: Free tissue transfer was used to address chronic deformities and diabetic foot disease in 41 patients. It required 44 microvascular flaps. The patients were 64.3 years old on average. Revascularization was needed in 18 individuals. Two microvascular flaps were required for 3 individuals. The supramicrosurgical approach was applied in 6 cases. Results: Two flap losses resulted in amputation. Due to serious infection or bypass failure, 4 additional patients needed to have their legs amputated within 6 months of their surgeries. Four further patients passed away within a year of their repair. All of the other patients were ambulated. Conclusion: By transferring free microvascular myocutaneous or fasciocutaneous tissue, large foot deformities can be repaired. However, small free microvascular flaps can be used in the case of abnormalities that are too small to be covered by local flaps and expose tendons or bones. The morbidity at the donor site is relatively minimal with these flaps. Another method for defect closure is venous flaps that have been arterialized. Amputation lowers quality of life and increases the risk of postoperative mortality